AI for Digital Marketing - Muhammad Edrick Abhiseka; Riyandi; Yongki Alex; Riza Ardy Saputra; Adi Setiawan (CV. Media Digital Publikasi Indonesia, 2024)
The rapid development of artificial intelligence (AI) technology has revolutionized the digital marketing landscape, enabling marketers to improve efficiency, personalization and strategic decision making. This research aims to map research trends related to the application of AI in digital marketing through bibliographic analysis. Qualitative research methods with a historical approach are used to collect and analyze scientific articles from leading international journals. Bibliometric analysis was performed with VOSviewer software to visualize patterns and clusters of key terms. Results show a significant increase in the number of publications related to AI in digital marketing, with a focus on topics such as marketing strategy, customer experience, social media, e-commerce and industrial marketing. The visualization reveals the interrelationships and groupings of various terms, providing insight into the current research landscape. This study contributes to the understanding of trends, opportunities and challenges in integrating AI into digital marketing practices. These findings are useful for researchers and practitioners to identify future research directions and develop effective marketing strategies by leveraging AI. However, further research is needed to explore the ethical implications, data security and other aspects regarding the application of AI in the context of digital marketing